Competency Prescriptions by Social Media Platforms and the Rise of Organizational Professionalism Among Content Creators - Haygert Pithan, Liana; Araujo, William Fernandes; Dalmoro, Mateus (AoIR Selected Papers of Internet Research, 2026)
This study contributes to platform and digital labor studies by examining how social media platforms (SMPs) manage content creators (CCs) through “organizational professionalism.” Julia Evetts (2013), an author on the neo-Weberian sociology of professions, has proposed this seminal ideal-type as a heuristic construct to address management discourse that disciplines workers through mechanisms of occupational identity and self-control, such as standardization, goal setting, and performance indicators. Organizational professionalism is demonstrated by describing competencies, which are the achievements, outputs, or deliveries generated when individuals mobilize and combine relevant resources to fulfill professional demands in a particular context (Le Boterf, 2000). Using a grounded theory approach (Charmaz, 2014), we analyzed 400 text and video transcripts of sessions instructing content creators on Instagram, TikTok, and YouTube to identify the competencies recommended by SMPs. The data analysis revealed 52 competencies arranged into eleven groups. Finally, we structured the data in accordance with Gioia et al.’s (2013) recommendations, identifying three aggregate dimensions of competencies: (1) complying with usage and monetization rules, (2) strategic content production and audience management, and (3) navigating creative and emotional challenges. Each competency dimension addresses the platform’s interests and is critical to the creator’s career prospects. So organizational professionalism works as a subtle but effective way to keep creators in line with the business goals of the platform while still giving the impression of independence and entrepreneurship. By doing so, SMPs not only overburden content creators but also shape the new occupation.